Erodibilidade em entressulcos, escoamento superficial e formação de crosta em solos representativos do Estado da Paraíba - Nascimento, Rodolpho José de Almeida (2019)
The understanding of the relationships involved in the water erosion process is the goal of everyone who deals with environmental degradation and the agricultural losses caused by it. In order to assist in the development of soil preservation strategies and containment this type of erosion, the present study aimed to: Chapter I) determine the characteristics of surface runoff and the determination of interill erodibility of the evaluated soils; establish correlations between physical and chemical properties of soils and Ki, in order to establish a mathematical model for their prediction; apply existing models for indirect estimation of Ki and evaluate its applicability to the soils of this study. Chapter II) indirectly evaluate surface sealing and crust formation through changes in hydraulic variables and soil interill erodibility. Four soils were evaluated: Ferralsol (FR); Acrisol (AC); Leptosol (LP); Luvisol (LV). The selection criterion was based on the degree of pedogenetic development. The interill erosion experiments were conducted under simulated rainfall, in laboratory conditions, with uncovered soil and plot slope of the 0.10 mm-1. The tests were carried out in experimental plots, with a useful area of 0,3481 m², where it was carried out tests with simulated rains, with mean intensity adjusted in 85 mm h-1 for 75 min. Simulated rains were applied at three consecutive events at 7 day intervals (Periods 0, 7 and 14 days) to determine the effects of surface sealing during rainfall and crust formation after the soil drying period on plot. Soil loss rates (PSi), suspended sediment concentration, flow rate, soil disaggregation rate (Di), characterization of hydraulic flow variables and soil interill erodibility (Ki) were evaluated. The flow regime in all soils was characterized as slow or subcritical laminar and the occurrence of interril erosion was confirmed. In Chapter I, it was possible to conclude that physical and chemical characteristics of each soil had a more direct influence in the understanding of the behavior of hydraulic variables of the surface runoff and the interill erodibility than the degree of pedogenetic development; among the evaluated soils, Luvisol (LV), although one of the least developed soils, was the most stable, with the lowest PSi, Di and Ki values; the existing models applied for indirect estimation of Ki were not adequate for all evaluated soils; the model suggested in this study proposes the use of the DMPAU and the Feo to estimate Ki in soils with the same characteristics of the evaluated soils. In Chapter II, it was conclude that formation of sealing and surface crusts were observed with increase of the flow velocity and liquid discharge, and the decrease of the height of the water sheet, as well as in the changes in PSi, Di and Ki, being in the first event of simulated rainfall the greater contribution to formation of superficial crusting; the LV showed the most stable after the successive events of simulated rainfall, even though the surface roughness was modified, did not present significant changes in the concentration of suspended sediment, total soil losses, maximum disaggregation rate and soil interill erodibility.